Public evaluation of streetscape in Kuala Lumpur City Center, Malaysia - Soltani, Soha (2017)
Physical elements, mainly landscape features shape streetscapes of cities. The review of literature demonstrates that pride, symbolism, attachment, memorability, recognizability, and fulfilment are the attributes of images of a street associated with people’s experience and perception. The problem pursued in this study is that inconsistency among physical elements weakens images of streets in the city center of Kuala Lumpur. Hence, the study aims at enhancing the images of streets in the City Center of Kuala Lumpur. The objectives of the study are: (1) to identify the existing physical elements of Tuanku Abdul Rahman (JTAR) and Bukit Bintang Streets (JBB) for improving the imageability of the city center of Kuala Lumpur, and (2) to determine the role of physical elements in forming the images of Tuanku Abdul Rahman (JTAR) and Bukit Bintang (JBB) Streets in making the city center of Kuala Lumpur more imageable. In light of the objectives aforementioned, the researcher employed a sequential mixed method to gather the data. First, a systematic observation study documented the real condition of physical elements of the two streets. Followed by that, a self-administered questionnaire survey investigated public evaluation of physical elements of streetscapes in the study areas. To strengthen the findings, the data gathered from both methods were converged through triangulation method. The researcher chose 330 participants via the time interval sampling method from passers-by, shoppers, workers, office workers, shopkeepers, shop-owners, and local residents who were familiar with study areas. The results demonstrated that transparency and seating spaces contributed to memorable images of streets in the city center of Kuala Lumpur the most and the least respectively. This study falls under a practical urban study that offers insights into development of future streetscapes. The findings present pragmatic suggestions that assist urban designers in bringing psychological comfort into urban contexts.